Bowel Preparation: Nursing Assessment, Patient Education, and Evidence-Based Perioperative Management - Almuairfi, Asya Ali; Murifah Dhahi Aljohani; Norah Muhaysin Sawwan Alanazi; Mona Hamad Ahmad Awaji; Abduallaziz Jarallah Obied Alenzi; Nahed Thani Alruwaili; Jawharah Abdulrhman Hamad Bin Muaddi; Zahra Kadim Ibrahim Alhalal; Joudi Ahmed Zayed Asiri; Eman Abdulmohsen Alsaleh; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Bowel preparation is essential for high-quality colonoscopy, enabling accurate mucosal visualization and reducing missed lesions. Inadequate cleansing compromises diagnostic reliability, increases procedural risks, and necessitates repeat examinations. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To review nursing roles in bowel preparation, focusing on assessment, patient education, and evidence-based perioperative management to optimize outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes current evidence on bowel preparation regimens, contraindications, risk factors, and nursing interventions. It examines pharmacologic classifications (isosmotic, hypoosmotic, hyperosmotic), dosing strategies, and interprofessional collaboration. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> High-volume polyethylene glycol (PEG) remains the safest option for complex patients, while low-volume PEG with ascorbic acid improves tolerability but requires caution in G6PD deficiency. Sulfate-free PEG enhances palatability without compromising efficacy. Hyperosmotic agents (magnesium citrate, sodium sulfate) and sodium phosphate carry significant risks, particularly in renal impairment and electrolyte imbalance. Split-dose regimens consistently outperform single-dose schedules in cleansing quality and adenoma detection. Nursing interventions—risk assessment, education reinforcement, hydration monitoring, and early escalation for intolerance—are pivotal for success. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective bowel preparation is a structured, team-based process integrating individualized regimen selection, patient-centered education, and vigilant nursing oversight. Optimizing preparation quality improves diagnostic accuracy, reduces repeat procedures, and enhances patient safety.